KEBERLANJUTAN USAHA BUDIDAYA UDANG VANAME DI KAWASAN KONSERVASI MANGROVE LAMPUNG MANGROVE CENTER (LMC) KECAMATAN LABUHAN MARINGGAI LAMPUNG TIMUR - Rifai, Muhamad; Arifin, Bustanul; Endryanto, Teguh (Lampung University, 2023)
The purposes of this research are to determine the income level of vanname shrimp farming, the value chain of vanname shrimp, and the sustainability of vanname shrimp farming in Marga Sari Village in Labuhan Maringgai Sub-District economically, socially, and environmentally by analyzing the financial feasibility of vanname shrimp farming. The data was collected on March 2020 using a census method. The data used are primary data from questionnaires and secondary data from literature studies. The results show that the income of vanname shrimp farming in Marga Sari Village is Rp210.493.641,03 per hectare per year. The value chains of vanname shrimp activities are inbound logistics, operations, out bound logistics, marketing and sales, but there are no after-sales service activities. There are two channels of agribusiness value chain of vanname shrimp which are formed in Marga Sari Village, namely channel I : farmer, collector trader, wholesale market trader; channel II : farmer, trader, exporter. The vanname shrimp farming in Marga Sari Village is sustainable, with a sustainability index of 82.22% for economic aspect, 90.63% for social aspect, and 99.00% for environmental aspect.